Projecting the Potential Impact of COVID-19 School Closures on Academic Achievement - Kuhfeld, Megan; Soland, James; Tarasawa, Beth; Johnson, Angela; Ruzek, Erik; Liu, Jing (Educational researcher, 2020)
As the COVID-19 pandemic upended the 2019–2020 school year, education systems scrambled to meet the needs of students and families with little available data on how school closures may impact learning. In this study, we produced a series of projections of COVID-19-related learning loss based on (a) estimates from absenteeism literature and (b) analyses of summer learning patterns of 5 million students. Under our projections, returning students are expected to start fall 2020 with approximately 63 to 68% of the learning gains in reading and 37 to 50% of the learning gains in mathematics relative to a typical school year. However, we project that losing ground during the school closures was not universal, with the top third of students potentially making gains in reading.